(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Multidrug-resistant Escherichia coli has become a global health threat, with limited effective treatment options. The growing prevalence of resistance poses significant challenges in managing these infections. This study aims to investigate the antibiotic resistance profiles of E. coli isolates collected from clinical samples. In this study, we biochemically characterized 48 E. coli isolates (using MIU, KIA, and Citrate tests) collected from clinical samples at a hospital in Dhaka City, Bangladesh. We then analyzed the antibiotic sensitivity patterns of these isolates against eleven different antibiotics (ten individual antibiotics and one combination), namely Ampicillin, Cefixime, Levofloxacin, Tobramycin, Doxycycline, Aztreonam, Ceftazidime, Nitrofurantoin, Piperacillin, Fosfomycin, and the antibiotic combination Co-trimoxazole (Sulfamethoxazole + Trimethoprim). The E. coli isolates showed significantly reduced susceptibility to most of the antibiotics tested. Only two antibiotics–Tobramycin (75%) and Fosfomycin (83%)-demonstrated significant effectiveness against the E. coli isolates. Necessary steps should be taken to prevent E. coli from acquiring further resistance to the remaining effective antibiotics, especially considering that ampicillin showed the highest resistance rate at 96%, whereas Fosfomycin exhibited the lowest resistance at only 17%. Dhaka Univ. J. Pharm. Sci. 25(1): 21-28, 2026 (June)